Agriculture in the City of Jerusalem "The Ayyubid period" as a model (583H - 648H / 1187 - 1250) - Awwad, Shadi Mohammad (Journal of Humanities & Social Sciences, 2020)
This study deals with the talk about agriculture in the city of Jerusalem, "the Ayyubid era as a model, which was represented in the study of agriculture and its conditions in terms of the nature of the land and the conditions of agriculture in the city of Jerusalem, and talked about the land used in that era, methods of land investment, irrigation sources and methods. The study discussed the most important crops produced in the city of Jerusalem, and then mentioned the most important animals and machinery used by the farmers in the city. The researcher has sought in this study to adopt the information contained in this study from considerable primary sources, despite the lack of resources and studies that dealt with the subject, and the researcher has proven in this study the reality and importance of agriculture in the city of Jerusalem in particular, and this is what the researcher stated contrary to what the Israeli occupation claims that Palestine was a barren country without agriculture.